2015
DOI: 10.1111/1467-9817.12052
|View full text |Cite
|
Sign up to set email alerts
|

Oral reading fluency and comprehension in Kenya: reading acquisition in a multilingual environment

Abstract: Reading research has shown that variable relationships exist between measures of oral reading fluency and reading comprehension, depending on whether the language of the text is the reader's first language or an additional language. This paper explores this phenomenon, using reading assessment data for 2,000 Kenyan children in two or three languages: English, Kiswahili and one of two mother tongues, Dholuo or Gikuyu. The assessment data allowed us to compare reading and comprehension rates across languages. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(37 citation statements)
references
References 40 publications
1
35
1
Order By: Relevance
“…These findings suggest that, when measuring children's vocabulary at a very young age, an assessment of mother tongue receptive vocabulary provides a strong indication of overall language ability, while LOI receptive vocabulary does not provide a full assessment of vocabulary development. Our findings are consistent with existing work in the study area, in which children demonstrated greater reading fluency in English than in Luo, but significantly lower reading comprehension scores in English than in Luo (Piper, Schroeder, et al, ). While children's familiarity with English through their classroom exposure is high, their actual understanding of English is often quite low (Trudell & Piper, ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings suggest that, when measuring children's vocabulary at a very young age, an assessment of mother tongue receptive vocabulary provides a strong indication of overall language ability, while LOI receptive vocabulary does not provide a full assessment of vocabulary development. Our findings are consistent with existing work in the study area, in which children demonstrated greater reading fluency in English than in Luo, but significantly lower reading comprehension scores in English than in Luo (Piper, Schroeder, et al, ). While children's familiarity with English through their classroom exposure is high, their actual understanding of English is often quite low (Trudell & Piper, ).…”
Section: Discussionsupporting
confidence: 92%
“…The adapted MDAT are the raw scores from the Kenya adaptation of the Malawi Developmental Assessment Tool (MDAT). Luo (Piper, Schroeder, et al, 2016). While children's familiarity with English through their classroom exposure is high, their actual understanding of English is often quite low (Trudell & Piper, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, language of instruction policies should cease to describe minority languages as problems to be overcome by abandoning them in favor of dominant languages; this would open a debate of how schools could include minority languages of instruction as a right for all children and as a resource to foster more equitable learning (see, for example, Piper, Schroeder, & Trudell, 2016).…”
Section: Teachers' Perspectives On Curriculummentioning
confidence: 99%
“…Another eminent line of work has shown that (text or oral) reading fluencythe ability to read connected texts with accuracy, speed and expressionis likewise critical to reading comprehension (Fuchs et al, 2001;Jenkins et al, 2003;Kim, 2015b;Kim, Park, & Wagner, 2014;Kim, Petscher, & Foorman, 2015;Kim, Petscher, Schatschneider, & Foorman, 2010;Kim, Wagner, & Lopez, 2012;Kuhn et al, 2010;Kuhn & Stahl, 2003; National Institute of Child Health and Human Development [NICHD], 2000;Roehrig et al, 2008), including in sub-Saharan Africa (Piper, Schroeder, & Trudell, 2015). Theoretically, text reading fluency is related to reading comprehension, because fluent reading affords readers the cognitive fundssuch as working memory and attentionto be used for essential comprehension processes (Kim, 2015b;Kim & Wagner, 2015;LaBerge & Samuels, 1974;Samuels, 2006).…”
mentioning
confidence: 99%